Developing Solution Processable Distributed Bragg Reflectors for Polaritonic Applications - Papachatzakis, Michail (My University, 2024)
In the pursuit of advancing electromagnetic confinement and manipulating physical phenomena, Quantum Electrodynamics and polaritons have emerged as pivotal concepts. Polaritons, which result from strong coupling between light and dipole-carrying excitations like excitons, play crucial roles across various scientific disciplines, including chemistry, quantum computing, and optoelectronics. Optical microcavities, defined by their resonance and quality factor (Q-factor), are key to enhancing polariton formation. While metal-clad microcavities and dielectric structures like Distributed Bragg Reflectors (DBRs) are prevalent, their fabrication through Physical Vapor Deposition (PVD) poses challenges in cost and complexity. Consequently, there is a growing interest in solution-processable methods for DBRs and microcavities, which promise simplicity, cost-effectiveness, and scalability. This thesis explores the development of solution-processable DBRs and microcavities using an in-house automated dip-coater. By alternating PVA/TiOH as high refractive index material and Nafion as low refractive index material, we manage to fabricate photonic structures such as a simple DBR structure, a fully dielectric microcavity, and a hybrid microcavity integrating solution-processed DBRs with PVD-deposited metal mirrors and TDAF excitonic materials. Overall, this research demonstrates the feasibility and effectiveness of solution-processable photonic structures in enabling practical applications of polaritons, thereby expanding the possibilities for future optoelectronic devices.
Keywords: Polaritons, Distributed Bragg Reflectors, Microcavities, OLEDs